What is Islamic Hotel? A Simple Additive Weighting Method - Murtadho, Fuad Shiddiq; Fadhillah, Muhammad Ivan; Nashir, Said Abdul; Khalid, Muhammad Nur Risqi; Abbad, Athallah Aqilah (Halal Tourism and Pilgrimage, 2023)
Halal tourism or halal industry is a tourism concept that focuses on the maqosid sharia values in it which are usually divided into: Hifdz Addin (religion), Hifdz nafs (soul), Hifdz aql (reason), Hifdz nasl (offspring), and hifdz Bi'ah (environment).Indonesia was awarded the first rank in the field of the best halal tourist destinations in the world according to the Global Muslim Travel Index (GMTI) 2023 report. The method used in this research uses qualitative methods. In this qualitative method will use the SAW (Simple Additive Weighting) method commonly known as the weighted summation method. This method is carried out with the type of data here carried out qualitatively which makes two research objects namely Noor In and Harris Hotel lodging. In interviews and recording methods through the web, newspapers, and journals, the results of the above research are data on the assessment of maqasid sharia indicators in sentul area hotels. Of these two hotels consist of harris hotel and Noor In inn. We get a reverse comparison of various aspects of maqasid sharia indicators in the fields of hifdz maal and hidz nashl. The first object is the Noor-In inn which has a value of 0.8333 and explains that this value gets the highest accreditation, namely A because it has a value between 0.75 - 1. While the second object is the Harris Sentul hotel which has a value of 0.3889 and states that this value has a maqaosid sharia accreditation of C or Fair maqosid sharia because it has between 0.25 - 0.49.